(untitled) (Encuentros, 2023)
The present scientific article exhibits the results of an investigation that examines the cinematographic product Encanto under the intention of identifying the categories that shape the identity of the Colombian subject. In response to the proposed, there developed a content analysis of the full-length film and of the cinematographic planes to which the personages and his respective behaviors limited themselves. It is proposed that the film presents an animated social construction of an innovative nature. The results confirm the proposal distinguishing cooperation, kindness, love, and the alternation between emotionality and reasoning as categories that profile the national individual.